Assessment of Customer Satisfaction in the Higher Education Institution Using SERVQUAL Model - Musandiwa, Joseph; Rikhotso, Sandile (Acta Universitatis Danubius. Œconomica, 2024)
Abstract: The paper aims to assess customer satisfaction with the administrative services provided to students of a particular University in South Africa using the SERVQUAL model. Service quality plays an integral role in the higher education institution’s reputation, competitiveness and most importantly in students’ satisfaction. A quantitative, descriptive approach was conducted to determine the level of students’ satisfaction with the administration services that is rendered by particular university’s central administration offices. 288 students participated in the study and a self-administered online and physical questionnaire were utilised to collect data. The findings revealed that the students are dissatisfied with the level of quality administration services provided by the University’s central administration offices across all dimensions of the SERVQUAL model. This was determined by the low perceptions scores of service quality as compared to the expectations scores. The paper recommends improvement of service quality so as to enhance the student satisfaction. Further, it is suggested that the university needs to invest on modern day equipment, advanced and secure technologies as well as training of staff in order to provide satisfactory services to the university’s principal stakeholders which are the students.